Layout Redesign to Eliminate Stagnation Using Blocplan to Increase Production Efficiency - Danny Wicaksono; Indra Setiawan; Fitriana Lestari Hasan (OPSI, 2022)
The rapid growth of the automotive industry was also followed by growth in subsidiary companies. One of the subsidiary companies is a company that produces auto parts such as wheels. Sales volume in 2021 increased to more than 2 million products while for 2022 to April it was more than 1 million products. High demand is not accommodated due to inadequate production capacity, one of which is the machining area. This study aims to increase efficiency by redesigning the layout of the factory which is considered to increase production results in the machining area. The method used in this research is Block Layout Overview with Computerized Planning using Logic and Algorithm (Blocplan). The results showed that the redesign of the machining area could reduce stagnation by adding 1 unit of multi drill machine. Relayout in the machining area can reduce 93” time stagnation for the K2SA rear ABS type which can produce 2 outputs at once. The delay in the machining area can be reduced from 4,863 seconds to 0 seconds.